2003
DOI: 10.1034/j.1399-6576.2003.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in drug effects: implications for anesthesiologists

Abstract: These examples illustrate that gender should be taken into account as a factor that may be predictive for the dosage of several anesthetic drugs. Moreover, there is an obvious need for more research in this area in order to further optimize drug treatment in anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
2
37

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(186 citation statements)
references
References 122 publications
(115 reference statements)
4
143
2
37
Order By: Relevance
“…Recently, several reports have demonstrated sex differences for propofol, with the average time of emergence after anesthesia shorter in females than in males 10)21)30) 31) , suggesting that males have a higher susceptibility to propofol than females 32) . Several studies have also demonstrated significantly higher levels of the propofol metabolites propofol glucuro- .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several reports have demonstrated sex differences for propofol, with the average time of emergence after anesthesia shorter in females than in males 10)21)30) 31) , suggesting that males have a higher susceptibility to propofol than females 32) . Several studies have also demonstrated significantly higher levels of the propofol metabolites propofol glucuro- .…”
Section: Discussionmentioning
confidence: 99%
“…Because males have more muscle and females have more fat, this would be expected to affect the distribution and times of emergence of a lipid soluble drug such as propofol, with shorter times of emergence in females 32) . In our study, there were significant differences in BMI between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutische Wirkungen Bei Frauen können vergleichbare analgetische Wirkungen mit geringeren Dosen an Opiaten als bei Männern erzielt werden [23,24]. Dies wird auf eine vermehrte Expression von Opioid-Rezeptoren zurückgeführt [25].…”
Section: Pharmakodynamikunclassified
“…-com as criações tecnológicas, culturais e folclóricas do próprio homem em sua vivência comunitária e cósmica: eletricidade, magnetismo, ultra-som, calor, música, agulha, massagem, religiosidade, espiritualidade, meditação, jogo, realidade virtual, auto-sugestão, riso, toque das mãos, entre outras 3,[6][7][8][9][10][11][12][13] . Os dados demográficos de cada paciente -idade, sexo, raça -também interferem na resposta dolorosa e na sua expressão clínica: desde o nascimento a criança sente dor; a mulher é mais resistente ao fenômeno doloroso, embora apresente mais efeitos secundários na sua cronicidade; além disso, já é anedótica a resistência à dor dos pacientes orientais com relação aos latinos [14][15][16][17] . Diante de uma dor persistente, métodos da AAA podem ser verificados no paciente antes dos farmacológicos consagrados desde que as intervenções cirúrgicas sejam a última opção terapêutica.…”
Section: Adjuvant and Alternative Analgesiaunclassified
“…-and technological, cultural, and folk creations in community and cosmic living: electricity, magnetism, ultrasound, heat, music, needle, massage, religiosity, spirituality, meditation, games, virtual reality, selfsuggestion, laughter, and touch of hands among others 3,6-13 . The demographic data for each patient -age, gender, race -also interfere with the response to pain and its clinical expression: the child experiences pain since birth; women have a higher pain threshold, although they present more secondary effects in its chronicity pain; besides, the resistance to pain of Oriental patients when compared to Latin is anedoctal [14][15][16][17] . When faced with a case of chronic pain, one should use AAA methods before the classical pharmacological methods, and surgical treatment should be the last option.…”
Section: Introductionmentioning
confidence: 99%